2013
DOI: 10.1056/nejmoa1216064
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Sources of C. difficile Infection Identified on Whole-Genome Sequencing

Abstract: Over a 3-year period, 45% of C. difficile cases in Oxfordshire were genetically distinct from all previous cases. Genetically diverse sources, in addition to symptomatic patients, play a major part in C. difficile transmission. (Funded by the U.K. Clinical Research Collaboration Translational Infection Research Initiative and others.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
603
3
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 598 publications
(658 citation statements)
references
References 38 publications
39
603
3
8
Order By: Relevance
“…Recent epidemiological studies have also shown that in addition to CDI patients, asymptomatic carriers and unknown sources of C. difficile are important contributors to new CDI cases. [10][11][12]27 Patients can develop CDI through 3 different infection histories: they can be admitted with CDI (CO-CDI), be admitted as colonized patients and become diseased during the hospital stay, or become both colonized and diseased patients during the hospital stay. Preventing CDI for these different timelines likely requires different prevention strategies (eg, note.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent epidemiological studies have also shown that in addition to CDI patients, asymptomatic carriers and unknown sources of C. difficile are important contributors to new CDI cases. [10][11][12]27 Patients can develop CDI through 3 different infection histories: they can be admitted with CDI (CO-CDI), be admitted as colonized patients and become diseased during the hospital stay, or become both colonized and diseased patients during the hospital stay. Preventing CDI for these different timelines likely requires different prevention strategies (eg, note.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Similarly, Curry et al 12 found that CDI cases were as frequently linked to transmission from asymptomatic as to symptomatic patients. Therefore, the contribution of symptomatic cases to transmission and new infection is likely to be lower than previously thought.…”
mentioning
confidence: 98%
“…Because of the difficulties with ribotyping, there has been a move towards sequencing and in silico MLST as a substitute (Dingle et al, 2011). The limited amount of whole genome sequencing-based epidemiological data currently available nearly all comes from Oxfordshire, UK (Didelot et al, 2012;Dingle et al, 2014;Dingle et al, 2011;Eyre et al, 2013), although there have been smaller scale studies performed elsewhere in the world.…”
Section: Accepted Manuscript 16mentioning
confidence: 99%
“…Complicating the epidemiology, it is estimated that up to a third of new CDI cases are community onset; 26,27 only 35% of inpatient CDI were linked to other hospital cases when investigated with whole genome sequencing. 28 …”
Section: Clostridium Difficile Infectionmentioning
confidence: 99%